2008
DOI: 10.1002/ejic.200800432
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of CoFe2O4 Hollow Spheres

Abstract: CoFe 2 O 4 hollow spheres with sizes ranging from 600 nm to 1 µm were prepared through hydrothermal treatment of an aqueous solution containing glucose, ammonium iron (II)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 41 publications
(36 reference statements)
0
33
1
Order By: Relevance
“…To the best of our knowledge, there have been only three reports on the synthesis of hollow nanospheres composed of ternary metal oxides. For instance, Chen and his coworkers demonstrated the preparation of CoFe 2 O 4 hollow spheres by hydrothermal reaction of a solution of metal oxide precursors and glucose, followed by calcination [15]. Tada et al reported the synthesis of hollow ferrite nanospheres with diameter of 220-340 nm by depositing ferrite shell layers on the surfaces of silica spheres by oxidation of Fe 2+ using NaNO 3 as an oxidizing agent in solution [16].…”
Section: Introductionmentioning
confidence: 98%
“…To the best of our knowledge, there have been only three reports on the synthesis of hollow nanospheres composed of ternary metal oxides. For instance, Chen and his coworkers demonstrated the preparation of CoFe 2 O 4 hollow spheres by hydrothermal reaction of a solution of metal oxide precursors and glucose, followed by calcination [15]. Tada et al reported the synthesis of hollow ferrite nanospheres with diameter of 220-340 nm by depositing ferrite shell layers on the surfaces of silica spheres by oxidation of Fe 2+ using NaNO 3 as an oxidizing agent in solution [16].…”
Section: Introductionmentioning
confidence: 98%
“…Chen et al [27] prepared NiFe 2 O 4 hollow nanospheres with diameter in the range of 90-180 nm via direct hydrothermal decomposition of a gel of Ni-Fe-EG (EG = ethylene glycol) in water solution. Chen and co-workers [28] The purpose of our study is to synthesize monodispersed purified hollow ferrite spheres in low temperature from EG solution with simple template free solvothermal method. Cobalt chloride and ferric chloride were used as cation sources in the reaction system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research on the novel sensing materials for further improving the performances of sensors is a hot topic. Spinel ferrites (AFe 2 O 4 , A=Zn, Ni, Cu, Cd, Co), in which the transition metal cation A 2+ is incorporated into the lattice of the parent structure of (Fe 2+ Fe 2 3+ O 4 ) [16], are already A c c e p t e d M a n u s c r i p t 4 widely applied in a variety of fields [17][18][19][20][21][22][23], which attributes to their environmental friendliness, low …”
Section: Introductionmentioning
confidence: 99%